Nuclear Grades based on Lens Opacities Classification System III associated with Phacoemulsification Parameters and Postoperative Central Corneal Thickness: Oral Presentation - Observational Study - Resident - MARIA DEBORA NIKEN LARASATI; Dicky Hermawan; Indri Wahyuni; Dianawati Koesoemawardhani (Majalah Oftalmologi Indonesia, 2023)
Abstract Introduction & Objectives : To determine association of nuclear cataract grades based on Lens Opacities Classification System (LOCS) III with phacoemulsification parameters and postoperative Central Corneal Thickness (CCT) and visual acuity. Methods : This was a prospective observational study in patient with uncomplicated senile cataract who gave consent and underwent phacoemulsification. Institutional Ethics Committee clearance was taken for the study. Preoperative nuclear cataract was evaluated using Lens Opacities Classification System (LOCS) III. Only nuclear grading NO and NC was obtained. All procedures was performed using peristaltic phaco machine and in the bag IOL implantation. Phacoemulsification parameters (US Total Time and CDE) were noted and compared in different grades of cataract. CCT change was recorded at day one after surgery. Results : Forty-six patients were evaluated. The mean USTT was 120.85 (56-252) seconds, mean CDE was 21.10 (5.70 – 43.38), and mean CCT change after surgery was 81.54(27 – 240). Nuclear grading of LOCS also had linear correlation with US Total Time (NO p<0.001, r=0.734; NC p<0.001, r=0.790) and CDE (NO p<0.001, r=0.728; NC p<0.001, r=0.685). There was significant correlation between CCT change with postoperative VA (p=0.002, r=0.443) and CDE (p<0.001, r= 0.553). CCT change also correlate with nuclear opacity (p=0.012, r=0.367) and nuclear color (p=0.035, r=0.312). Conclusion : Nuclear grading of LOCS III related to the amount of time and energy used in phacoemulsification, and also CCT change after surgery as a qualitative measurement of corneal edema. Increasing postoperative CCT affected patient's visual acuity after cataract surgery.